2007
DOI: 10.1007/s11665-006-9005-z
|View full text |Cite
|
Sign up to set email alerts
|

Tensile, Compression and Fracture Properties of Thick-Walled Ductile Cast Iron Components

Abstract: The article presents the outcome of a comprehensive program of tensile, compression and fracture toughness experiments, addressing thick-walled ductile cast iron inserts used for the production of three nuclear waste canisters. The resulting data are required as input to the assessment of the failure probability of the canisters. Moreover, these data are useful for the improvement of the casting technique as such. Although the same material specification is always used, material properties are found to show si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 1 publication
2
18
0
Order By: Relevance
“…It can be noted that the very long solidification time and the resulting microstructural alterations lead to low values of tensile strength and total elongation in comparison to conventional ferritic DCI; for instance, with respect to thick-walled (t > 60 mm) EN-GJS-400-15, the reduction in tensile strength and total elongation is about 20% and 75%, respectively. The yield-stress-to-tensile-strength ratio approaching the unity further denotes a very brittle material behavior, while, as expected, the yield stress is little affected [4], being the yield stress compliant with the minimum prescription of 240 MPa for EN-GJS-400-15. The results of the rotating bending fatigue tests are summarized in Table 4.…”
Section: Monotonic and High-cycle Fatigue Propertiessupporting
confidence: 72%
See 1 more Smart Citation
“…It can be noted that the very long solidification time and the resulting microstructural alterations lead to low values of tensile strength and total elongation in comparison to conventional ferritic DCI; for instance, with respect to thick-walled (t > 60 mm) EN-GJS-400-15, the reduction in tensile strength and total elongation is about 20% and 75%, respectively. The yield-stress-to-tensile-strength ratio approaching the unity further denotes a very brittle material behavior, while, as expected, the yield stress is little affected [4], being the yield stress compliant with the minimum prescription of 240 MPa for EN-GJS-400-15. The results of the rotating bending fatigue tests are summarized in Table 4.…”
Section: Monotonic and High-cycle Fatigue Propertiessupporting
confidence: 72%
“…Casting large volume parts of weight on the order of tens of tons is particularly critical as the control of the final microstructure is rather difficult [3][4][5]. Consequently, solidification defects cannot be completely avoided, their presence must be somehow tolerated and different strategies are pursued to limit their detrimental effects.…”
Section: Introductionmentioning
confidence: 99%
“…Karsay and E. Campomanes [4][5][6][7][8][9] studied the influence of silicon content on ductile iron, and found that lower silicon content can reduce the performance of chunky graphite iron, especially in its capacity to demonstrate good impact performance at low temperatures. The proper content of silicon can increase the nodularity and improve the mechanical properties of heavy section ductile iron, and inhibit graphite floatation and chunky graphite formation [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The nodular cast iron grade EN-GJS-400-18-LT, in which graphite spheroids or nodules in a ferritic matrix provide large ductility and fatigue strength, is widely used. Specific shape of the graphite in the ferritic microstructure acts as the crack arrester and lowers the stress intensity in front of the crack, which makes it an appropriate material for such cyclically loaded structures [1][2][3][4][5]. Therefore, in order to prevent catastrophic failures and to prolong the service lifetime of wind turbine structures, it is important to consider the influence of the graphite nodule geometrical features (size, shape and distribution of nodules) on the fatigue crack initiation and propagation at the root of a geometrical discontinuity and local notches.…”
Section: Introductionmentioning
confidence: 99%